La cuestión filosófica de la expansión del universo - Sacchi, Mario Enrique (Sapientia, 2006)
In the first half of the 20th century, several astronomers and cosmologists propose the theory of the uniform expansion of the universe. Researches due to Friedmann, Hubble, Humanson, Lemal-tre and other authors stand out in maintaining such a theory. But all these academics upheld a cosmogonic interpretation of the expanding universe based only in the observation of local motion, particularly of galaxies. The main problem of their interpretation lies in the non existence of an empty space where those galaxies can expand themselves, for the universe itself contains all places and no other ones exist out of our natural world to be occupied by other bodies, whether the littlest one or the now the huge one. But it is evident that the universe seems to expand, so that it is necessary to know how philosophy can save the appearances of its expansive motion. In this article we try to save these appearances, but in addition to the local motion, we also hold that the universe also expands by means of other kinds of motions, viz. generation or coming to be and increase. Furthermore, an expansion towards an infinite empy space is plainly rejected as impossible. The paper finishes with an affirmation of the created condition of prime matter as something which cannot be studied within the limits of positive sciences, because it is an expedient reserved to metaphysics and sacred theology exclussively.